Novel macrocyclic and acyclic ligands for metal ion coordination - design, synthesis and physical evaluation - Nolan, Claire (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
Supramolecular chemistry is a relatively young discipline dating back to the late 1960s and early 1970s and, as such, is a highly diverse and dynamic field incorporating organic, inorganic and physical chemistry. Much of the inspiration and origins of supramolecular chemistry comes from the chemistry found in living biological systems. The overlap of disciplines helps us understand and mimic the biological processes in nature using synthetic means with the emphasis on the recognition and targeting of physiologically important species. Chapter one will detail the history and development of supramolecular chemistry with the main focus being on lanthanide luminescence.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin